Clinical Outcome of Superselective Transarterial Embolization for Acute Colonic Gastrointestinal Bleeding: A Retrospective Single-Center Experience - Behera, Rajendra Kumar; Narang, Mohak; Pandey, Shivam; Madhusudhan, Kumble Seetharama (Journal of Clinical Interventional Radiology ISVIR, 2025)
Purpose The aim of the study was to assess the safety and efficacy of transarterial embolization in the treatment of acute lower gastrointestinal hemorrhage (LGIH) from colonic origin and to determine factors that influence the treatment outcome.Methods This retrospective study included 32 patients (mean age: 37.5 years; 24 males) of acute LGIH with a colonic source diagnosed on conventional angiography between March 2014 and May 2023. The clinical characteristics at presentation, laboratory findings, etiology of bleeding, angiographic findings, and embolization details were assessed and correlated with outcomes comprising success rates of embolization, complications, recurrence (immediate and late), and mortality.Results Embolization was technically successful in 27 patients (84.4%) and clinically successful in 24 patients (75%). Embolic agents used were coils (n = 12), n-butyl cyanoacrylate glue (n = 8), Gelfoam (n = 4), polyvinyl alcohol (PVA) particles (n = 2), and a combination of coils and glue (n = 1). Major complications were seen in five patients (15.6%) including artery dissection (n = 3) and catheter impaction and fracture (n = 2). Sixteen patients (50%) died after a mean period of 8.3 ± 8.8 days mostly due to septic shock related to the underlying cause. Immediate recurrence was observed in five patients (15.6%) after 3.8 ± 1.6 days of embolization and late recurrence in one patient (3.1%) after 76 days. Both univariate and multivariate analyses showed that acute pancreatitis as etiology was significantly associated with mortality (p < 0.05). No other parameters showed any significant association with outcomes.Conclusion Transarterial embolization is safe and effective in the treatment of acute LGIH due to a colonic source. The etiology of acute pancreatitis is significantly associated with increased mortality.
Keywords: lower GI bleed; transarterial intervention